Application of Consignment Sales Accounting for Ardiles Brand Shoes at PT Ramayana Bali Mall in Ponegoro - I Gusti Agung Ayu Intan Fatmayoni; Ni Wayan Dian Irmayani; Desak Made Indah Paramitha Sari; Helena Vilomena Iju (PT FORMOSA CENDEKIA GLOBAL, 2024)
PT. Ramayana Bali mall is a retail company engaged in the department store which has many branches in Indonesia. In addition to department stores that sell clothing products such as clothes, Ramayana also has a supermarket or supermarket that sells daily food neds this study aims to mall complies with financial accounting standards. The type of research used in this study is a qualitative descriptive approach. This study uses interviews and documentation of the parties responsible for recording consignment accounting. Based on the application of consignment accounting based on financial accounting standards, it can be concluded that PT. Ramayana Bali Mall hos not fully implemented consignment sales recording repots based on financial accounting standards in the income statement. We recommend that you record the sales of the consignment based of financial accounting standards, namely recording with a separate method to make it easier to calculate the profit obtained from the sale of the consigment